(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe the clinical characteristics and imaging diagnosis of patients with giant cell tumor of bone undergoing surgery for bone graft. Subjects and methods: Retrospective descriptive study on 38 patients with confirmed diagnosis of giant cell tumor of bone who underwent surgery to remove tumor and bone graft at VietDuc University Hospital from January 2015 to December 2020. Results: The three most common sites of giant cell tumors of bone were the lower end of the femur, the lower end of the radial bone, and the top of the tibia. 97.4% of the lesions appeared on the long bones. 65.8% of the lesions appeared on the right half of the body. 100% of cases reported pain at the tumor site. Lesions on X-ray were graded according to Campanacci was 3 (7.9%) grade I, 16 (42.1%) grade II and 19 (50.0%) grade III. Conclusion: The three most common sites of giant cell tumors of bone were the lower end of the femur, the lower end of the radial bone and the top of the tibia. All cases had pain at the tumor site. Lesions on X-ray according to Campanacci were graded I, II, III 7.9%, 42.1% and 50.0%, respectively.